Development of Interpenetrating Network (IPN) hybrid composite for thin film protection - Seah, Geok Leng. (2012)
Anti-biofouling aims to prevent the acculumulation of biological organisms like proteins and micro-organisms on surfaces. This can be achieved by applying anti-biological and fouling release non-toxic polymeric coatings on surfaces. Conventional production of polymer composites is a time consuming process which involves a long thermal curing step of the monomers into thermosets. An attractive cost saving and environmentally friendly alternative is to perform curing via UV radiation. It shortens the curing time greatly, lowers the curing temperature and requires little or no solvent. Thus, it is increasingly popular in the coating and microelectronic industries. Acrylates and other radical initiated monomers are widely studied and used in industry. However, they are highly sensitive to oxygen and have poor adhesion strength on many surfaces, making them poor coatings. By contrary, epoxides are more stable in oxygen and have good adhesion properties, establishing them as good coatings for many surfaces. Unfortunately, they are not as well studied and hence not widely used. It is desired to create an IPN of both epoxides and acrylates to retain the advantages of the individual polymers while increasing the hardness, impact strength and chemical resistance to produce a good anti-biofouling coating. Nanofillers are commonly added into polymer matrix to improve various properties of the materials. Hence, nanocomposites of TMPT(EO)A added with different nanofillers were UV-cured and studied kinetically. DPC was used to carry out the curing with the analysis of curing kinetics and photoreactivity simultaneously. Surface energy, tensile strength and hardness of the IPNs were analyzed via static water contact angle measurement, tensile test and Vicker micro hardness test.